Eating disorder inventory in the assessment of psychosocial status in the obese patients prior to and at long term following biliopancreatic diversion for obesity - Adami, Gian Franco; Gandolfo, Patrizia; Campostano, Adelia; Bauer, Beatrice; Cocchi, Florio; Scopinaro, Nicola (The International journal of eating disorders, 1994)
Psychological traits of obese patients, assessed with the Eating Disorder Inventory (EDI), were compared to those of subjects in the long term following biliopancreatic diversion for obesity (BPD), when body weight has been steadily normal for over 1 year and any preoccupation with dieting and weight has been completely abandoned. The overall results suggest that the stable body weight normalization on a completely free diet does confer considerable psychological benefit on obese individuals. On the basis of the EDI results, post-BPD subjects were divided into weight-preoccupied and not-weight-preoccupied individuals. In the not-weight-preoccupied subjects, the psychosocial status and emotional reactivity were closely similar to those observed in lean control persons, whereas the few weight-preoccupied subjects, in spite of completely normal body weight, showed residual body dissatisfaction and personality traits very similar to those of eating-disordered patients.